Clinical Characteristics and Mortality-Associated Factors in Trauma Patients Undergoing Permanent Versus Temporary Tracheostomy - Ahmad K. Alnemare (Clinics and Practice)
Objective: This study evaluated the characteristics, outcomes, and mortality-associated factors in patients who underwent tracheostomy after traumatic injury to optimize clinical decision-making and patient care in critical trauma settings. Materials and Methods: A retrospective cohort analysis was conducted using the National Trauma Data Bank (NTDB) records from 2013 to 2016. This study included 41,630 adult trauma patients who underwent tracheostomy procedures. Data analysis included descriptive statistics, univariate comparisons, and multivariate logistic regression analyses. The study protocol adhered to STROBE guidelines for observational studies. Results: Analysis of the total cohort revealed that patients with tracheostomy demonstrated high rates of severe injuries (75.2%) and a notable comorbidity burden, including cardiovascular disorders (4.0%) and blood disorders (5.8%). Multivariate analysis revealed that mortality risk was independently associated with advanced age (OR 1.018, 95% CI 1.016–1.021), higher injury severity scores (OR 1.004, CI 1.002–1.007), female sex (OR 1.187, CI 1.078–1.308), and cardiovascular surgical intervention (OR 1.487, CI 1.350–1.638). Among the study population, 7.6% underwent permanent tracheostomy procedures, with these patients showing some distinct clinical characteristics in terms of injury severity and comorbidity profiles. Conclusions: This comprehensive analysis demonstrates the complex clinical characteristics and mortality-associated factors in trauma patients requiring tracheostomy. Key factors influencing survival outcomes include age, injury severity, sex, and cardiovascular surgical intervention. These findings provide valuable insights for clinical decision-making and risk assessment in trauma patients requiring tracheostomy. The observed differences between permanent and temporary tracheostomy patients warrant further investigation with more detailed timing and indication data.